KONSELING KELOMPOK REALITAS UNTUK MEREDUKSI NOMOPHOBIA PADA SISWA KELAS XC SMAN 1 BANTUL TAHUN 2023 - Hartuti (Jurnal Riset Daerah, 2023)
Best practice in reality group counseling aims to reduce Nomophobia in students. The method used is descriptive qualitative. Data obtained based on observation, implementation of reality group counseling and questionnaires. The subjects of this study were students in class XC SMA Negeri 1 Bantul. Based on the best practices in reality group counseling, the following were carried out: Explaining material about Nomophobia to teenagers or generation Z, group discussions about nomophobia, student presentations about nomophobia, and reality group counseling. Based on the results of the questionnaire and reality group counseling, students were able to reduce the nomophobia they experienced